Assessment of mental health among hospital-discharged patients of COVID-19 in North India: A cross-sectional study - Preeti Kour; Manmeet Singh; Bhavna Sahni (Archives of Mental Health, 2023)
Background: Psychological impact of COVID-19 is an emerging area of interest among researchers worldwide. We aimed to study the prevalence of anxiety and depression among COVID-19 survivors and its association with individual characteristics including demographic variables. Methods: One hundred and fifty COVID-19 survivors from a tertiary care hospital were contacted to collect information regarding anxiety and depression using the Generalized Anxiety Disorder-7 (GAD-7) scale and Patient Health Questionnaire-9 (PHQ-9). The Pearson's Chi-square was used for univariate analysis of categorical variables. The Mann–Whitney test was used to check the significance between group medians. Results: 21.3% of the survivors (n = 32) reported postdischarge COVID-19 anxiety. Mild, moderate, and moderately severe anxiety was reported by 17.3%, 3.3%, and 0.7% of the patients, respectively, on using the GAD-7 questionnaire. PHQ-9 revealed that 29.3% (n = 44) had depression. Minimal, mild, moderate, and moderately severe depression was reported by 19.3%, 24.0%, 2.0%, and 3.3% of the respondents, respectively. None of the survivors had severe anxiety or depression. In both the questionnaires, variation in median scores was statistically significant with age, whereas for GAD-7 scores, the difference in median scores was statistically significant only for gender. On analysis, age above 40 years was a statistically significant determinant for both anxiety (P = 0.041) and depression (P = 0.018) while male gender showed a statistically significant association in case of anxiety (P = 0.028). The correlation between age and respective scores and GAD-7 scores and PHQ-9 scores was also found to be significant (P < 0.001). Conclusion: These preliminary screening results provide convincing evidence of anxiety and depression among COVID-19 survivors, thus reiterating the need of timely detection and management of mental health issues through formulation of strategies to tackle the concurrent psychological comorbidities amid the ongoing pandemic.